Supporting the care of children with diabetes in school: a qualitative study of nurses in the UK. Issue 7 (7th March 2013) - Marshall, M.; Gidman, W.; Callery, P.
Abstract Aims Intensification of diabetes management in children and young people has implications for schools. The aim of this study was to examine the role of nurses in supporting care of children with diabetes in schools and early years settings. Methods The qualitative design incorporated focus groups and individual telephone interviews with nurses who were unavailable to participate in focus groups. A purposive sample of 47 nurses from acute and community settings, participated in eight focus groups and eight telephone interviews. Data were analysed through a process of constant comparison. Results Nurses identified an ambiguous and inadequate legal and policy framework. The responses of schools were variable and unpredictable because the views of head teachers determined the level of cooperation. School staff could lack basic knowledge about Type 1 diabetes. Relationships between school staff and parents could also affect their willingness to provide support for diabetes care. The skills of negotiating appropriate support for children with diabetes were learnt by experience rather than through formal training or evidence‐based guidance. Nurses' accounts demonstrated uncertainties about: what could be required of schools; how schools would respond; individual responsibilities; and about what constituted best practice. Conclusions There is a need for more evidence about how healthcare providers can influence schools and about the most cost‐effective use of nurses to support the management of children with diabetes in schools.